Developing a blended learning approach for the effective teaching of electronic circuit analysis - Paul Holland (IEEE, 2016)
The use of modern ICT technology has revolutionized the way that universities perform their teaching and learning role. Recent high profile MOOCs have shown that e-learning approaches can attract large numbers of students to study subjects such as electronic circuits. However, high dropout rates and concerns about quality mean that it is unlikely that e-learning techniques alone can meet the industrial demand for high calibre engineers. The aim of this work was to understand if the use of a blended learning approach would be a better option and enhance student abilities to analyse electrical and electronic circuits by providing them with additional e-learning resources. It was found that was possible to match the format of e-lectures to lectures to capture well known teaching methods that increase student learning. Student engagement with the e-lectures was very high and they have given good feedback about their experience of using them.